Health workforce policy and plan implementation in the context of universal health coverage in the Africa Region. (19th May 2022) - Ahmat, Adam; Okoroafor, Sunny C; Asamani, James Avoka; Dovlo, Delanyo; Millogo, Jean Jacques Salvador; Abdou Illou, Mourtala Mahaman; Nyoni, Jennifer
Abstract : Several countries in Africa have developed human resources for health (HRH) policies and strategies to synergise efforts in setting priorities, directions and means to address the major challenges around leadership and governance, production, recruitment, management, motivation and retention and coordination. In this paper, we present information on the availability, quality and implementation of national HRH policies and strategic plans in the WHO Africa Region. Information was obtained using a questionnaire completed by the head of HRH departments in the Ministries of Health of 47 countries in the WHO Africa Region. Of the 47 countries in the Region, 57% (27 countries) had HRH policies and 11% (5 countries) were in the process of developing one. Thirty-two countries (68%) had national strategic plans for HRH with 12 (26%) being in the process of developing a strategic plan, and 28 countries reporting the implementation of their strategic plans. On the quality of the policies and strategic plans, 28 countries (88%) linked their plans to the national development plan, 30 countries (94%) informed their policy and plan using the national health policy and strategic plans. Evidence-based HRH policies and plans guide the actions of actors in strengthening health systems. Countries need to invest in developing quality HRH policies and plans through an intersectoral approach and based on contextual evidence. This is vital in ensuring that equitably distributed, well-regulated and motivated HRH are available to deliver people-centred health services to the population.